2021
DOI: 10.7759/cureus.19695
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Augmented Feedback on Motor Learning: A Systematic Review

Abstract: In motor learning, augmented feedback (AF) is the information provided by sources outside the body and encompasses visual feedback, auditory feedback, and multimodal augmented feedback. This review aims to examine the most recent evidence on these different modality types in healthy and diseased populations and athletes. The reporting of this review was guided by the standards of the “Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA)” statement with the aim to examine the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Visual feedback was used in studies by Biénkiewicz et al ( 82 ), Butki and Hoffmann ( 34 ), An et al ( 33 ), and Smith et al ( 42 ). Many studies have shown that multimodal feedback in particular, i.e., the combination of two or more forms of feedback, can help to improve performance and can be superior to a single form of feedback [for reviews see ( 81 , 102 )]. However, multimodal augmented feedback has not yet been investigated in golf so far.…”
Section: Discussionmentioning
confidence: 99%
“…Visual feedback was used in studies by Biénkiewicz et al ( 82 ), Butki and Hoffmann ( 34 ), An et al ( 33 ), and Smith et al ( 42 ). Many studies have shown that multimodal feedback in particular, i.e., the combination of two or more forms of feedback, can help to improve performance and can be superior to a single form of feedback [for reviews see ( 81 , 102 )]. However, multimodal augmented feedback has not yet been investigated in golf so far.…”
Section: Discussionmentioning
confidence: 99%
“…Given the multiple facets of exergaming and rehabilitation, future refinements of the TARPP-Q may consider extending the number of items dedicated to the theme (including a more structured reference to Virtual Reality and Augmented Reality), to provide a fine-grained analysis of the phenomenon [60,61].…”
Section: Limitations and Future Developmentsmentioning
confidence: 99%
“…Feedback is used to optimize motor learning in different age groups [ 1 , 2 , 3 ]. In essence, motor learning feedback is based on providing information about the performance of an action or task to the practitioner (i.e., the person who performs the action/task), which is used as a basis for improvement [ 4 ].…”
Section: Introductionmentioning
confidence: 99%